2015
DOI: 10.3750/aip2014.45.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Ponticola iranicus sp. nov. (Actinopterygii: Perciformes: Gobiidae) from the Caspian Sea basin

Abstract: Background. Five species of Ponticola have hitherto been recognized among freshwater gobies in the Ponto-Caspian basin. In 2014 a number of specimens representing this genus were collected in northern Iran. The detailed morphological and karyological study of those gobies collected revealed signifi cant differences between them and their known congeners. The aim of this study was to describe these fi sh as a new species from the Caspian Sea basin. Materials and methods. The fi sh specimens were collected in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Proterorhinus sp. and P. nasalis ), the CBH is also the stage of endemic evolution for another Ponto‐Caspian gobiid genus Ponticola Iljin, 1927: Ponticola iranicus and Ponticola patimari endemic to the Iranian part of the CBH, Ponticola cyrius endemic to the Kura River, Ponticola constructor and Ponticola rhodioni endemic to the south and north of the Bzyb Range, respectively, and Ponticola rizensis and Ponticola turani endemic to the İyidere and Aksu streams of Turkey, respectively (Miller, 2003; Kovačić & Engin, 2008; Vasil'eva, Mousavi‐Sabet & Vasil'ev, 2015; Eagderi, Nikmehr & Poorbagher, 2020). Apart from the fact that their conservation status, like other Caucasian freshwater fish, has been incompletely assessed (Freyhof et al, 2020; IUCN, 2021), the known genetic, biological, ecological and distributional data on these species are also insufficient and systematic observations are needed for taking steps towards conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Proterorhinus sp. and P. nasalis ), the CBH is also the stage of endemic evolution for another Ponto‐Caspian gobiid genus Ponticola Iljin, 1927: Ponticola iranicus and Ponticola patimari endemic to the Iranian part of the CBH, Ponticola cyrius endemic to the Kura River, Ponticola constructor and Ponticola rhodioni endemic to the south and north of the Bzyb Range, respectively, and Ponticola rizensis and Ponticola turani endemic to the İyidere and Aksu streams of Turkey, respectively (Miller, 2003; Kovačić & Engin, 2008; Vasil'eva, Mousavi‐Sabet & Vasil'ev, 2015; Eagderi, Nikmehr & Poorbagher, 2020). Apart from the fact that their conservation status, like other Caucasian freshwater fish, has been incompletely assessed (Freyhof et al, 2020; IUCN, 2021), the known genetic, biological, ecological and distributional data on these species are also insufficient and systematic observations are needed for taking steps towards conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Ponticola kessleri (Günther, 1861) and P. gorlap (Iljin, 1949) are euryhaline and are able to inhabit the sea as well as a wide range of freshwater habitats. In addition, there are several real freshwater endemics including P. constructor (Nordmann, 1840), P. cyrius (Kessler, 1874), P. iranicus Vasil'eva et al, 2015 , P. patimari Eagderi et al, 2020 , P. rhodioni (Vasil'eva & Vasil'ev, 1994), P. rizensis (Kovačić & Engin, 2008 ), P. turani (Kovačić & Engin, 2008 ), and P. hircaniaensis Zarei, Esmaeili, Kovačić, et al, 2022a , all endemic to small areas in the Caucasus Biodiversity Hotspot (CBH). Ponticola cyrius is endemic to the Kura River drainage from headwaters in Turkey down to Azerbaijan, P. constructor and P. rhodioni are endemic to the south and north of the Bzyb Mountain Range, respectively, P. rizensis and P. turani are endemic to the İyidere and Aksu streams in Turkey, respectively, and P. iranicus , P. patimari , and P. hircaniaensis are endemic to small areas of the Iranian part of CBH (Eagderi et al, 2020 ; Kovačić & Engin, 2008 ; Miller, 2003 ; Vasil'eva et al, 2015 ; Zarei, Esmaeili, Kovačić, et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Neilson and Stepien ( 2009a ) placed P. iljini with P. gorlap in their revised phylogenetic systematic classification, however, Vasil'eva et al ( 2016 ) proposed the validity of P. iljini in a karyological analysis but also restricted its distribution to the west coast of Kazakhstan, northern Caspian Sea. Morphological and karyological examination of Ponticola specimens from the Sefidrud and Gisum rivers in Iran by Vasil'eva et al ( 2015 ) identified noticeable differences with other species of Ponticola including P. cyrius , which led to the description of P. iranicus . Phylogenetic and species delimitation analyses of the south Caspian gobiids by Zarei, Esmaeili, Schliewen, et al ( 2021b ) only supported the presence of two species, P. gorlap and P. iranicus in the freshwater habitats of the SCB, indicating that the fishes previously identified by Ahnelt and Holčik ( 1996 ) as P. cyrius and P. iljini were in fact conspecific with P. iranicus and P. gorlap .…”
Section: Introductionmentioning
confidence: 99%
“…The Caspian Sea basin belongs to the Ponto–Caspian biogeographical region, encompassing the basins of the Black, Azov, Caspian, and Aral Seas (Coad, ). The native fish fauna of the Caspian Sea basin consists of an estimated 162 fish species, 100 of them being endemic species or subspecies (Miller, ; Vasil′eva, Mousavi‐Sabet, & Vasil′ev, ); many of them of commercial importance. The fishes of the family Gobiidae inhabiting the area are usually less important commercially and therefore knowledge on their biodiversity is far from being complete (Miller, ; Vasil′eva et al., ).…”
Section: Introductionmentioning
confidence: 99%